Sport, friendship, peace : Moskva, 1980 - Soldatkin, V (Плакат СССР (Plakat), 1979)
Globe with Moscow 1980 Summer Olympics' logo at the centre; colourful representation of the Olympic flame Poster advertising the 1980 Summer Olympics in Moscow PO-0411